2017
DOI: 10.1111/1556-4029.13477
|View full text |Cite
|
Sign up to set email alerts
|

The Griffiths Question Map: A Forensic Tool For Expert Witnesses’ Assessments of Witnesses and Victims’ Statements

Abstract: Expert witnesses are sometimes asked to assess the reliability of young witnesses and victims' statements because of their high susceptibility to memory biases. This technical note aims to highlight the relevance of the Griffiths Question Map (GQM) as a professional forensic tool to improve expert witnesses' assessments of young witnesses and victims' testimonies. To do so, this innovative question type assessment grid was used to proceed to an in-depth analysis of the interview of an alleged 13-year-old victi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Despite its obvious utility to interview training (Griffiths, 2008) and assessment (Dodier and Denault, 2018; Kopše, 2017), research on the GQM in the published literature has been somewhat limited. Walsh and Bull (2015), for instance, used the question type categories put forth by Griffiths and Milne (2006) and presented example maps, and they found that skilled interviews were associated with more productive questioning that produced more complete accounts from suspects.…”
Section: You Ask and Do Not Receive Because You Ask Wronglymentioning
confidence: 99%
“…Despite its obvious utility to interview training (Griffiths, 2008) and assessment (Dodier and Denault, 2018; Kopše, 2017), research on the GQM in the published literature has been somewhat limited. Walsh and Bull (2015), for instance, used the question type categories put forth by Griffiths and Milne (2006) and presented example maps, and they found that skilled interviews were associated with more productive questioning that produced more complete accounts from suspects.…”
Section: You Ask and Do Not Receive Because You Ask Wronglymentioning
confidence: 99%
“…In line with Phillips et al (2012), the authors for the present research categorised questions under the terms appropriate and inappropriate . The questions utilised by the Source Handler were coded in accordance with the coding scheme displayed in Table 1 (adapted from Wright & Alison, 2004; Dodier & Denault, 2018; Griffiths & Milne, 2006; Oxburgh et al, 2010; Powell & Snow, 2007; Waterhouse et al, 2018). With regard to minimal encouragers , if they were followed by a question, only the question was coded as it was that utterance which gathered the intelligence (e.g., “uh huh [ minimal encourager not coded], what colour was the car?…”
Section: Methodsmentioning
confidence: 99%
“…The content of the interviewers' and the children' utterance types were then coded. We coded the interviewers' utterances using the Griffiths Question Map coding scheme (Griffiths & Milne, 2006; see also Dodier & Denault, 2018). Interviewer's utterances were first coded as either (i) appropriate; that is being child-centered and adapted to the individual characteristics of the child (language, active mental images) and thus in turn supporting more complete and accurate recall, or (ii) inappropriate; that is utterances limiting completeness and accuracy of recall (cf.…”
Section: Methodsmentioning
confidence: 99%